Variations of Science Learning Teaching Aids Using Kits and Sensors: A Systematic Literature Review - Bayu Septiawan; Gunawan Gunawan; Erin Ryantin Gunawan (Indonesian Publication Center, 2026)
The rapid development of science and technology requires science learning to focus not only on conceptual understanding but also on the development of science process skills, critical thinking, and technological literacy. One approach to addressing this challenge is the use of science learning teaching aids based on kits and sensors. This study aims to systematically review the variations of science teaching aids developed and implemented in previous studies, focusing on the types of kits and sensors, science domains, and their impact on students’ learning outcomes. This research employed a literature review method using a systematic literature review approach. Relevant articles were identified through Google Scholar and ResearchGate databases. A total of 25 selected articles were analyzed descriptively based on tool characteristics, applied technologies, and key research findings. The results indicate that kit- and sensor-based teaching aids, particularly those integrating microcontrollers and digital sensors, significantly enhance students’ conceptual understanding, science process skills, and higher-order thinking skills. Furthermore, these teaching aids effectively support experiment-based, inquiry-oriented, and STEM learning approaches. Therefore, science learning teaching aids based on kits and sensors demonstrate strong potential as innovative and contextual tools to improve the quality of science education.